DAMPAK SERTIFIKASI GURU TERHADAP PENINGKATAN KUALITAS PENDIDIKAN PADA MADRASAH TSANAWIYAH DI SULAWESI SELATAN - Amiruddin Amiruddin (Balai Penelitian dan Pengembangan Agama Makassar, 2017)
This research uses quantitative approach by using sampling quota as many as 155teachers who have been certified in Madrasah Tsanawiyah. A total of 103questionnaires were distributed in Makassar City, and 52 questionnaires weredistributed in Jeneponto Regency using Likers 4 scale to 101 items. The resultsshowed that based on the homogeneity analysis of maximally achieved data of 394and the minimum value of 245, yielded an average value of 335. 52, with a standarddeviation of 30,526. besides the effect of teacher certification on the improvement ofmadrasah quality shows that: The involvement in the planning process of highcategorizedmadrasah program (2.55). Involvement in the implementation of highcategorizedmadrasah programs (2.96). The impact on the improvement of thecategorized learning process is very high with the average of 3.84. While the impacton the increase in the competence of fellow teachers is also categorized very highwith the average of 3.66. The use of teacher certification funds if linked to family andpersonal interests is more aimed at financing children's education, and for the sake ofhealth (buying drugs / vitamins), and maintaining the appearance (buying clothes,bags, and shoes). However, for the benefit of increasing the profession is more widelyused to participate in seminars and comparative studies, as well as on the provisionof professional support facilities are used to buy a computer and buy a book ofliterature supporting learning.